The effect of strategic planning in improving the efficiency of crisis management in Jordanian industrial companies - Al-Hababi, Salem Mohammed (Journal of Risk and Crisis Management, 2024)
The study aimed to identify the most prominent elements of strategic planning and its dimensions (diverse vision, strategic mission, and strategic objectives) in improving diversity management in Jordanian industrial companies, by following the descriptive and analytical formation. The study targeted people at the senior administrative levels (general managers and their deputies) and the middle administrative level (managers) in Jordanian industrial companies, whose number is estimated at approximately (145) managers. The data was collected initially through a questionnaire and distributed electronically to the elements of the analytical study and analyzed using descriptive statistics. Simple and mixed referral analysis and multiple hypotheses were also used. The study found that there was a statistically significant significance at the moral level (α < 0.05) for the strategic objectives in management efficiency in Jordanian industrial companies. The study recommended working to participate in the company's strategy, identifying potential scenarios of crises and challenges within the company's strategic planning, and managing the company's specific strategy to achieve its goals, and adapting it to adapt to new challenges and changes.
Keywords: Strategic Planning; Strategic Vision; Strategic Mission; Strategic Objectives; Crisis Management; Jordanian Industrial Companies